PENDIDIKAN KELUARGA MUSLIM DI TENGAH MASYARAKAT MULTI AGAMA: ANTARA SIKAP KEAGAMAAN DAN TOLERANSI (Studi di Desa Suro Bali Kepahiang-Bengkulu) - Idi Warsah (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
The article is the result of research triggered by the phenomenon of religious activities and tolerance attitude of Moslem communities in Suro Bali Village. This study aimed to find the information about the educational pattern of Moslem families in the middle of multi-religious community in Suro Bali village, Ujan Mas district, Kepahiang regency in instilling religious teachings and inter-religious tolerance. To obtain the informations, the researcher used a qualitative approach and found some matters as follow: First, the religious attitudes of Moslem communities in Suro Bali village has not been seen yet. This condition proven by the lack of understanding towards Islamic teachings, low-level of motivation in worship and other religious activities. And also, there is no limitation of interreligious relationships and marriages which cause the religious conversion then. Second, the forms of tolerance among religion, such as respecting and safeguarding each other in doing the worship, complimenting and visiting each other, and attending an invitation in the neighborhood. Third, the pattern of religious education for children in the family is by providing exemplary and knowledge to their children, both in home/individually and religious schools. Meanwhile, many tolerance educations were obtained by children through the social interactions in the community.